1993
DOI: 10.1001/archpsyc.1993.01820160050006
|View full text |Cite
|
Sign up to set email alerts
|

Panic Attacks During Placebo Procedures in the Laboratory

Abstract: Heart rate, respiratory measurements, and Acute Panic Inventory symptoms of 17 patients with panic disorder who experienced panic attacks during a placebo infusion (situationally provoked panic) were analyzed and compared with similar data from a group of 19 patients with panic disorder who panicked during lactate infusion. Previously, it was shown that the group with lactate-induced panic attacks exhibited increased minute ventilation compared with normal control subjects and nonpanicking patients with panic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…Our findings of an increase in RR during CCK-5-induced PA are also supported by results of other studies that used different panic challenges and that showed an increase in V T and RR during induced PAs (Gorman et al, 1988(Gorman et al, , 2001). Interestingly, Goetz et al (1993) have described a marginally significant increase in RR during PA induced by placebo infusion in PD patients, with a peak of the RR around the same time (30 s) as the peak in RR that we observed (40 s) (Figure 4). Another human study testing the effects of CCK-4 on airway resistance found no differences in spirometric variables after CCK-4-induced panic symptoms (Shlik et al, 1997).…”
Section: Discussionsupporting
confidence: 75%
“…Our findings of an increase in RR during CCK-5-induced PA are also supported by results of other studies that used different panic challenges and that showed an increase in V T and RR during induced PAs (Gorman et al, 1988(Gorman et al, , 2001). Interestingly, Goetz et al (1993) have described a marginally significant increase in RR during PA induced by placebo infusion in PD patients, with a peak of the RR around the same time (30 s) as the peak in RR that we observed (40 s) (Figure 4). Another human study testing the effects of CCK-4 on airway resistance found no differences in spirometric variables after CCK-4-induced panic symptoms (Shlik et al, 1997).…”
Section: Discussionsupporting
confidence: 75%
“…Goetz et al [1994] reported a high degree of symptom consistency and self-rated similarity between symptom arrays during a typical panic attack and lactate-induced panic. Addressing panic attacks somewhat closer to the experience of a natural panic attack, our group [Goetz et al, 1993] reported the physiological data from 17 PD patients who experienced "situationally provoked panic" during the saline infusion period of a lactate infusion protocol; however, individual symptom data were not reported at that time. These API-17 data (unpublished data available on request) are now available and indicates that the following symptoms differed from baseline to the point of panic (among patients experiencing these lactate-induced attacks) at the alpha level of 0.002: fear in general (effect size = 1.6); dyspnea (2.2); fear of dying (1.8); confusion (1.8); difficulty concentrating (2.5), doing one's job (2.1), and speaking (2.6); sweating (1.5); and twitching/trembling (3.3).…”
Section: Discussionmentioning
confidence: 99%
“…In previous publications, we have shown that prominent cardiorespiratory responses occur during situationally provoked (laboratory setting) panic attacks [Goetz et al, 1993], and that levels of baseline fear and dyspnea, as well as lactate-induced increments in fear and dyspnea, are the most salient features of the panic response to lactate infusion [Goetz et al, 1996]. Ley, in a series of reports [1987,1989,1992], noted the salience of fear and dyspnea in panic disorder, which he attributed to hyperventilation.…”
Section: Introductionmentioning
confidence: 89%
“…Even though the SNS is instrumental in the etiology of anxiety disorders, experimental evidence suggests that the PNS may be responsible for the maintenance of elevated physiology in psychopathology (15). For instance, the administration of catecholamine (SNS) antagonists prior to induced panic attacks does little to reduce heart rate, suggesting that the SNS plays a minor role in such attacks (19). However, lactate, which is a known suppressor of vagal (PNS) activity, accumulates during panic attacks (20), and is even administered in laboratory studies to induce panic attacks (21) and stimulate PTSD symptoms (22).…”
Section: Psychophysiology Of Ptsdmentioning
confidence: 99%